Seeking help for nightmares: associated personality factors - Schredl, Michael (Journal of sleep research, 2023)
Research indicated that patients suffering from nightmares are often undertreated. One reason for this gap is that nightmare sufferers themselves often have not sought professional help for their nightmares, and—if they did—it was not very helpful. The current study aimed at studying trait factors (personality, harm avoidance) in relation to the persons considering seeking professional help. In a population-sample of 1108 persons (712 women, 396 men) with a mean age of 50.55 ± 14.22 years, it was also found that only some of the persons who have problems with nightmares even considered seeking professional help as an option. As expected and after controlling for effects of nightmare frequency, persons with high harm avoidance and high introversion were more likely not seeking help for their problems with nightmares. The associations with low education, low agreeableness and low conscientiousness with considering seeking professional help might point to the fear of stigmatisation in nightmare sufferers. Interestingly, the association between harm avoidance and “Considering seeking professional help” was even stronger in the subsample of frequent nightmare sufferers (once a week or more often). Future efforts should aim at findings new ways to offer adequate help for nightmares and increase the knowledge about nightmare treatment in healthcare professionals.
Gesehen am 26.02.2024